Prognostic Factors Associated With Sleep Duration: Serum Pro-Oxidant/Antioxidant Balance and Superoxide Dismutase 1 as Oxidative Stress Markers and Anxiety/Depression - Susan Darroudi; Mostafa Eslamiyeh; Karrar Khaleel Jaber Al-Fayyadh; Mohammad Zamiri Bidary; Sina Danesteh; Aliakbar Hassanzadeh Gouji; Reza Assaran Darban; Habibollah Esmaily; Majid Ghayour-Mobarhan; Mohsen Moohebati; Gordon A. Ferns (Frontiers Media S.A., 2023)
Objectives: Sleep is a conserved vital behavior in humans, and insufficient sleep is associated with several disorders. Recent studies have investigated the association of sleep duration, oxidative stress markers, anxiety, and depression. Therefore, we aim to assess the relationship between sleep duration, serum pro-oxidant/antioxidant balance (PAB) and superoxide dismutase 1 (SOD1) levels as markers of oxidative stress, anxiety, and depression.Methods: Participants included in our cross-sectional analysis were recruited as part of the MASHAD study (n = 9,184). Nocturnal sleep duration was identified using a self-reported questionnaire, and serum pro-oxidant/antioxidant balance (PAB) and superoxide dismutase 1 (SOD1) levels were assessed using methods that have been previously reported.Results: Serum PAB, depression, and anxiety scores were found significantly higher in subjects with very short sleep duration. In an adjusted model using MANOVA regression analysis, serum PAB was significantly higher in the subjects with a very short sleep duration (p: 0.016 in depression and p: 0.002 in anxiety).Conclusion: The present cross-sectional study demonstrates a relationship between sleep duration, oxidative balance, and depression/anxiety, especially in anxiety subjects that might predict each other.